Artificial womb technology and clinical translation: Innovative treatment or medical research?. (29th November 2019) - Romanis, Elizabeth Chloe
Abstract: In 2017 and 2019, two research teams claimed 'proof of principle' for artificial womb technology (AWT). AWT has long been a subject of speculation in bioethical literature, with broad consensus that it is a welcome development. Despite this, little attention is afforded to more immediate ethical problems in the development of AWT, particularly as an alternative to neonatal intensive care. To start this conversation, I consider whether experimental AWT is innovative treatment or medical research. The research–treatment distinction, pervasive in regulation worldwide, is intended to isolate research activities and subject them to a greater degree of oversight. I argue that there is a tendency in the literature to conceptualize AWT for partial ectogenesis as innovative treatment. However, there are sufficiently serious ethical concerns with experimental AWT that mean that it must not be first used on humans on the basis that it is a 'beneficial treatment'. First, I outline the prospects for translation of AWT animal studies into treatment for human preterms. Second, I challenge the conceptualizations of experimental AWT as innovative treatment. It must be considered medical research to reflect the investigatory nature of the process and guarantee sufficient protections for subjects. Identifying that AWT is research is crucial in formulating further ethico‐legal questions regarding the experimental use of AWT. Third, I demonstrate that clinical trials will be a necessary part of the clinical translation of AWT because of requirements laid out by regulators. I consider the justification for clinical trials and highlight some of the crucial ethical questions about the conditions under which they should proceed.